Estudos genômicos em Cocos nucifera L.: construção de mapa genético, mapeamento de QTL de florescimento e seleção de marcadores informativos de ancestralidade em subvariedades de coqueiro anão - Alves, Wellington Bruno dos Santos (2023)
The coconut palm (Cocos nucifera L.) is known as the "tree of life" due to its importance in providing vital resources to millions of farmers, with diverse uses of its products. The coconut palm is a perennial, diploid monocotyledon (2n = 32), with a relatively large genome (1C = 2.74 Gb). It belongs to the Arecaceae family (Palmae) and is the only species in the genus Cocos. With its center of origin located between Southeast Asia and Melanesia, where it exhibits the greatest genetic diversity, the coconut palm is cultivated in more than 92 countries, covering over 12 million hectares worldwide. The plants of this species are divided into two groups based on morphology, genetic diversity, and predominant mode of reproduction. The tall coconut palm is more resistant, cross-pollinated, tall in stature, and late-flowering. In contrast, the dwarf variety is shorter, susceptible to pests and diseases, self-pollinating, with low genetic diversity, and early-flowering. Despite its global socioeconomic importance, advances in coconut breeding have been modest due to its perennial nature, long generational cycle, late flowering, and large tree size, which demand extensive experimental areas and long-term continuous investments. In the first part of the present study, a genetic map was built using an F2 population of coconut generated by open pollination between F1 hybrids originally generated by crossing the Brazilian Green Dwarf Jequi (BGDJ) and the West African Tall (WAT). The approach exploited the fact that the BGDJ variety is autogamous and highly homozygous, while the WAT variety is allogamous and genetically diverse. A high-density linkage map was constructed with approximately 3,000 DArTseq SNPs filtered for high quality, anchored on two independently published genomes assembled at chromosome scale. In the YANG genome, the linkage map covered the 1035 Mb of the genome constructed by short-read sequencing, corresponding to a coverage of approximately 43.14% of the 2400 Mb genome. In the WANG genome, which was more complete because it was constructed using Nanopore sequencing and chromatin contact technology (Hi-C), the genetic map covered 2382 Mb, representing 99.27% of the genome. In the second part of this work, taking advantage of the strong segregation for precocity traits in the F2, a major-effect QTL with incomplete dominance was mapped for flowering time (LOD score = 11.86). The FLOWERING LOCUS T (FT), previously reported to be involved in the control of flowering in coconut through alternative splicing variant analysis, was colocalized with the major effect QTL within a 200 kb window, providing evidence for its role as the functional variant underlying the distinction in flowering behavior between the Dwarf and Tall types. Major effect QTLs were also detected for plant development traits in the same genomic region, suggesting pleiotropism of the FT gene in relation to other precocity traits. In a third part of this study, dwarf and tall coconut accessions were genotyped via DArTseq for a detailed characterization of polymorphism between them, aiming to provide a genome-wide SNP resource for future use in diversity studies, genetic mapping and genomic selection in the genus. A catalog of 11,925 SNPs uniquely positioned in the 16 pseudochromosomes of the YANG reference genome was generated. Based on this SNP catalog, genomic regions of higher and lower genetic differentiation between cultivars were identified, focusing on dwarf coconut cultivars that historically display low differentiation. Finally, based on the distribution and differentiation of allele frequencies among the different cultivars, a set of 45 ancestry informative SNPs (AIM Ancestry Informative Markers) was selected, capable of recovering the same genetic structure obtained using all 11,925 SNPs and efficiently allocating individuals to their respective cultivars, as well as quantifying the genomic proportions of dwarf and tall genomes in a recombinant F2 hybrid generation.